The home economics extension program in Metro Manila - Gatuz, Remedios David; Orlina, Elsa A. (1989)
This study was conducted primarily to evaluate the extent of the effectiveness of the Home Economics Extension Program (HEEP) implemented in Metro Manila. Specifically, it endeavored to answer the following: 1. What is the profile of the Home Economics Extension trainors and trainees in terms of: a) age, b) civil status, c) number of children, d) ethnic orientation, e) educational background, f) occupation, g) approximate monthly income, h) length of involvement in the program? 2. Which of the objectives of the HEEP was given the greatest attention by the Home Management Technicians (HMT) and the Rural Improvement Club (RIC) Trainors? 3. How do the trainees perceive the objectives of the program during the implementation? 4. How do the trainees perceive the philosophy of the program during the implementation? 5. What media were used to implement the program and which one was most effective? 6. What teaching methods were used most often by the HMT and the RIC trainors during the training program? 7. What instructional materials were most often used by the Home Management Technicians and the Rural Improvement Club Trainors and how adequate are they? 8. What subject areas or components of the program were given the most attention considering the family problems in Metro Manila? 9. How effective is the Home Economics Extension Program in terms of its component areas: a) major programs, b) projects, c) special projects, d) special events? 10. How effective are the strategies for implementation of the Home Economics Extension Program like: a) Resource materials development/dissemination, b) home extension classes, c) home visits, d) researches, and e) linkages? 11. Is there a difference in the Home Economics Extension performance in the different locales (i.e., rural and urban), in Metro Manila? 12. What input and process variables influence the performance of the trainees in the HEEP? 13. What problems were met by both the trainors and the trainees during the program implementation? The following hypotheses were formulated in this study: 1. The Home Economics Extension Program is effective in its overall components. 2. There is a significant difference between the rural and urban barangays in terms of the effectiveness of the HEEP in Metro Manila. 3. Input and process variables significantly influence the performance of trainees in the HEEP in Metro Manila. This study utilized the "After-Only" design and was strengthened by adding a comparison group of respondents from each locale who were not given any training under the HEEP. These respondents were similar to the program recipients in terms of their socio-demographic characteristics... The following recommendations are given for further study and future action: a) younger and single participants both males and females should be encouraged to participate in the HEEP; b) an assessment of the needs and interests of the client groups should be undertaken to ensure program relevance of projects to the needs of the age groups, cultural or ethnic backgrounds; c) encourage people with white collar occupations to participate in the program; d) further attention should be given to agribusiness and income generating projects, e) strengthen further the promotion of the HEEP, to make it more effective among the urban participants. In conclusion, the HEEP has demonstrated potential in contributing its share in solving to a certain degree some of the social problems. Perhaps, an expansion of this program (HEEP) is deemed advisable to other barangays in order to improve the economic status of families and thus, will ultimately minimize the gravity of poverty, the roots of our social problems.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Typescript.
Keywords: Home economics extension work -- Philippines -- Manila Metropolitan Area